The Influence of Peer Group, Economic Literation and Use of Social Media on Consumtive Behavior of State Senior High School Students in Brebes - Khoiriyah, Ummamatul; Rusdarti, Rusdarti; Kardoyo, Kardoyo (Universitas Negeri Semarang, 2020)
Consumptive behavior is an act of consuming goods and services not based on needs but for mere desire and satisfaction. The purpose of this study is to analyze the influence of peer groups, economic literacy and the use of social media, both jointly and partially on the consumptive behavior of Social Sciences Department students at state senior high school students in Brebes. The research method used in this study is a quantitative method. The subjects of this study were all students of class X and XI majoring in social studies at SMA Brebes regency with a population of 664 students and then a random sample of 166 students was obtained. The data collection method uses a questionnaire that is tested for validity and reliability. Data analysis uses descriptive analysis and multiple linear regression analysis. The results of this study indicate (1) there is a peer group influence, economic literacy and the use of social media, together towards consumptive behavior by 79.30%, positive and significant effect, (2) peer group has a positive and significant effect on consumptive behavior by 29.05%. (3) economic literacy has a negative and significant effect on consumptive behavior of 21.34%, (4) the use of social media has a positive and significant effect on consumptive behavior of 9.86%. (5) The results of the regression equation Y = 57.029 + 0.239 X1 - 0.174 X2 + 0.123 X3. Conclusions, (1) there is a peer group positive influence on the consumptive behavior of State Senior High School students in Brebes economic literacy has a negative effect and the use of social media has a positive effect on consumer consumptive behavior (2) there is a peer group effect on consumptive behavior State Senior High School students in Brebes (3) there is a negative influence of economic literacy on consumptive behavior of students majoring in social studies State Senior High School students in Brebes (4) there is a partially positive influence on the use of social media on consumptive behavior of State Senior High School students in Brebes. Suggestions students are expected to choose peer group associations group well in conducting learning activities that are more beneficial for the future, economics teachers must instill about economic literacy so that students are not only expected to master the material, but can apply it in daily life, the need for collaboration between teachers and parents nature pay attention to students in the use of social media so that students use social media wisely and in accordance with their needs, this research is expected to make renewal by expanding the scope of research such as other factors that influence consumer behavior in students such as perception, motivation, culture, conditions parent's economy, and self control.